A liquid scintillator for thermal neutrons detection - Ding, Ya.; Gundorin, N.A.; Zhang, Zh.; Nemchenok, I.B.; Pikelner, L.B. (Functional Materials, 2009)
A novel gadolinium-loaded liquid scintillator based on linear alkylbenzene intended for use in a large-scale neutrino experiment Daya Bay has been studied. The study results show a high efficiency of thermal neutron detection using the novel liquid scintillator and make it possible to recommend this material in experiments on search for neutrino oscillations.